2024
DOI: 10.1101/2024.01.06.574477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Negative allosteric modulation of cannabinoid CB1receptor signaling suppresses opioid-mediated tolerance and withdrawal without blocking opioid antinociception

Vishakh Iyer,
Shahin A. Saberi,
Romario Pacheco
et al.

Abstract: The direct blockade of CB1cannabinoid receptors produces therapeutic effects as well as adverse side-effects that limit their clinical potential. CB1negative allosteric modulators (NAMs) represent an indirect approach to decrease the affinity and/or efficacy of orthosteric cannabinoid ligands or endocannabinoids at CB1. We recently reported that GAT358, a CB1-NAM, blocked opioid-induced mesocorticolimbic dopamine release and reward via a CB1-allosteric mechanism of action. Whether a CB1-NAM dampens opioid-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…In addition to the results presented here, a recent study from our lab also explored the application of the CB1R NAM GAT358 on antinociceptive and effects of morphine as well as morphine tolerance and naloxone-precipitated opioid withdrawal 27 . We showed that GAT358 did not impede morphine antinociception but was effective in reducing morphine tolerance as well as naloxone-precipitated opioid withdrawal 27 . As such, GAT358 provide new options for non-addictive pain management, as it produced antinociception on its own, and also potentially reduce the reliance and addiction liability of opioids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the results presented here, a recent study from our lab also explored the application of the CB1R NAM GAT358 on antinociceptive and effects of morphine as well as morphine tolerance and naloxone-precipitated opioid withdrawal 27 . We showed that GAT358 did not impede morphine antinociception but was effective in reducing morphine tolerance as well as naloxone-precipitated opioid withdrawal 27 . As such, GAT358 provide new options for non-addictive pain management, as it produced antinociception on its own, and also potentially reduce the reliance and addiction liability of opioids.…”
Section: Discussionmentioning
confidence: 99%